Role of agile methodology for software product development - Kharade, Jyoti; Prajapati, Sneha; Narkar, Dakshata; Kharade, Dhanaji S (International Journal of Computer Sciences and Engineering, 2025)
Increasing complexities in the requirements set on programming solution due to change in the business activities has lead to need of modern approaches, also known as agile methodologies also known as lightweight, which claim to provide solution to above said problem. Knowledge Management (KM) can be easily accepted into agile software development (ASD) environments. Agile software development processes include some practices that support Knowledge Management (KM). KM is about learning, and ASD set up an environment that supports learning processes. In this paper, attempt is made to study the role of Agile methodology in software development, find barriers in applying agile methodologies in software development and to propose the role of agile methodologies for enhancing software development.